Knowledge, care-seeking behavior, and factors associated with patient delay among newly-diagnosed pulmonary tuberculosis patients, Federal Capital Territory, Nigeria, 2010 - Biya, Oladayo (The African Field Epidemiology Network, 2014)
INTRODUCTION: Early treatment of Tuberculosis (TB) cases is important for reducing transmission, morbidity and mortality associated with TB. In 2007, Federal Capital Territory (FCT), Nigeria recorded low TB case detection rate (CDR) of 9% which implied that many TB cases were undetected. We assessed the knowledge, care-seeking behavior, and factors associated with patient delay among pulmonary TB patients in FCT. METHODS: We enrolled 160 newly-diagnosed pulmonary TB patients in six directly observed treatment short course (DOTS) hospitals in FCT in a cross-sectional study. We used a structured questionnaire to collect data on socio-demographic variables, knowledge of TB, and care-seeking behavior. Patient delay was defined as > 4 weeks between onset of cough and first hospital contact. RESULTS: Mean age was 32.8 years (± 9 years). Sixty two percent were males. Forty seven percent first sought care in a government hospital, 26% with a patent medicine vendor and 22% in a private hospital. Forty one percent had unsatisfactory knowledge of TB. Forty two percent had patient delay. Having unsatisfactory knowledge of TB (p = 0.046) and multiple care-seeking (p = 0.02) were significantly associated with patient delay. After controlling for travel time and age, multiple care-seeking was independently associated with patient delay (Adjusted Odds Ratio = 2.18, 95% CI = 1.09-4.35). CONCLUSION: Failure to immediately seek care in DOTS centers and having unsatisfactory knowledge of TB are factors contributing to patient delay. Strategies that promote early care-seeking in DOTS centers and sustained awareness on TB should be implemented in FCT.